Microcirculation physiotherapy pad
By using graphene air layer and fiber layer in the fabric components of the physiotherapy pad, and applying wear-resistant coatings with components such as aramid fiber, dopamine and silica on the surface, the problem of easy damage and insufficient wear resistance of the physiotherapy pad fabric is solved, achieving higher comfort and service life.
Patent Information
- Application Number
- CN202411617158.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-07
AI Technical Summary
After long-term use of existing physiotherapy pads, the fabric is prone to breakage, resulting in a decrease in comfort, insufficient wear resistance and short service life.
Graphene air layer and graphene fiber layer are used as the outer layer of the fabric component, and wear-resistant coating is applied to the surface of the graphene air layer. The wear-resistant coating contains components such as aramid fiber, dopamine and silica to form an wear-resistant layer.
Through the combination of graphene air layer and fiber layer, the moisture-absorbing, anti-static and antibacterial effects of the physiotherapy pad are improved, and breathable and comfortable are increased. At the same time, the wear-resistant layer significantly improves the wear resistance of the fabric and extends the service life of the physiotherapy pad.
Smart Images

Figure BDA0005132542990000071 
Figure BDA0005132542990000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of mattresses, and in particular to a microcirculation therapy mattress. Background Art
[0002] A therapeutic mat is a mattress that can promote blood circulation and improve microcirculation. When the body experiences fatigue, muscle tension, etc., a therapeutic mat can be used for appropriate relief, thereby improving the symptoms of discomfort.
[0003] When using a therapeutic pad, you usually need to lie on the mattress to improve your condition, so you need to be in contact with the pad for a long time, and generally the pad needs to be heated to achieve better therapeutic effects. However, long-term use and long-term contact with the pad will cause constant friction between your limbs and the fabric and the surface of the pad, which can easily lead to fabric damage, etc., which reduces the comfort of using the pad, so it needs to be improved. Summary of the invention
[0004] In order to improve the wear resistance of the physiotherapy pad, the present application provides a microcirculation physiotherapy pad.
[0005] The microcirculation therapy pad provided in this application adopts the following technical solution: A microcirculation physiotherapy pad comprises a physiotherapy component and a fabric component, wherein the fabric component is coated on the outside of the physiotherapy component, the fabric component comprises a wear-resistant layer, a graphene air layer, a graphene fiber layer, a silk-like cotton layer, a sanded fabric layer, a needle cotton layer, a sponge layer and a breathable layer, the physiotherapy component is located between the sanded fabric and the needle cotton fabric, the wear-resistant layer is obtained by coating a wear-resistant coating on the surface of the graphene air layer, and the wear-resistant coating comprises the following components in parts by weight: 500-560 parts of coating substrate, 60-70 parts of antibacterial slow-release microcapsules, 120-160 parts of wear-resistant components, 12-16 parts of softeners, and 10-16 parts of defoaming agents; The wear-resistant component includes aramid fiber, dopamine and silicon dioxide.
[0006] By adopting the above technical scheme, the graphene air layer and the graphene fiber layer are used as the outer layer of the fabric component, which can achieve moisture absorption and perspiration, anti-static and antibacterial effects, thereby promoting the effect of the therapeutic pad, and the above fabric layer is moderately soft and hard, and has excellent air permeability, which can effectively improve the comfort during use. At the same time, a wear-resistant coating is coated on the surface of the graphene air layer to form a wear-resistant coating on the surface of the graphene air layer, which can reduce the wear of the graphene air layer fabric, thereby improving the service life of the therapeutic pad; the wear-resistant component in the wear-resistant coating is prepared by compounding dopamine, aramid fiber and silica, which can make the wear-resistant component have good compatibility, and dopamine is coated on the surface of the aramid fiber to obtain a nano unit. After silica is generated on the surface, a wear-resistant component with hydrophobic properties is obtained, which improves the wear resistance and the overall mechanical properties of the coating.
[0007] Preferably, the wear-resistant component is prepared by the following method: The nano-aramid fiber is mixed with deionized water to obtain an aramid fiber dispersion, dopamine is added, the pH value is adjusted to alkaline, the reaction is stirred, and the reaction is washed to obtain dopamine-modified aramid fiber; the dopamine-modified aramid fiber is mixed with anhydrous ethanol, ammonia water is added, and after ultrasonication, the temperature is increased while stirring, and ethyl orthosilicate and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane are added under the stirring condition, and the stirring is continued for 4 hours, and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane is further added to keep stirring for 3 hours to obtain a wear-resistant component.
[0008] By adopting the above technical scheme, dopamine is coated on the surface of the aramid fiber, and nano-silica particles are in situ grown on the surface by tetraethyl orthosilicate, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane is used for low surface energy modification, so that the component has super hydrophobic properties, so that the prepared wear-resistant component has good wear resistance and mechanical properties, and has good hydrophobic properties, so that the prepared therapeutic pad has good wear resistance and breathability.
[0009] Preferably, the mass ratio between the aramid limiter and dopamine is 1:(1.12-1.18).
[0010] By adopting the above technical solution, preferably the mass ratio between dopamine and aramid fiber is within the above range, the stability of the prepared dopamine-modified aramid fiber can be further improved.
[0011] Preferably, the mass ratio between the dopamine-modified aramid fiber and tetraethyl orthosilicate is 1:(0.45-0.49).
[0012] By adopting the above technical solution, preferably the mass ratio between dopamine-modified aramid fiber and tetraethyl orthosilicate is within the above range, which can further improve the stability of the prepared dopamine-modified aramid fiber.
[0013] Preferably, the antibacterial sustained-release microcapsules include daylily essence polyvinyl alcohol and ε-polylysine.
[0014] Preferably, the antibacterial sustained-release microcapsules are prepared by the following method: The oil phase is obtained by mixing daylily essence with isophorone diisocyanate, polyvinyl alcohol is mixed with deionized water to obtain a polyvinyl alcohol dispersion, the polyvinyl alcohol dispersion is heated to a reaction temperature, the oil phase is added to the polyvinyl alcohol dispersion, an emulsifier and a chain extender are added and stirred to obtain a daylily essence prefabricated microcapsule emulsion; ε-polylysine is mixed with deionized water to obtain an ε-polylysine aqueous solution, the ε-polylysine aqueous solution is added to the daylily essence prefabricated microcapsule emulsion, the reaction temperature is maintained and stirred to obtain antibacterial sustained-release microcapsules.
[0015] By adopting the above technical scheme, the volatile components in the daylily essence are beneficial to human health, and can further enhance the effect of promoting human circulation when combined with a therapeutic pad. At the same time, it has an antibacterial effect and can synergistically inhibit bacteria with graphene fabrics. By preparing microcapsules with ε-polylysine and polyvinyl alcohol and encapsulating the daylily essence, the daylily essence can be slowly released and the occurrence of rapid oxidation and inactivation of the daylily essence can be reduced, so that the daylily essence can exert its effect for a long time. The surface roughness of the prepared microcapsules is improved, and they can be stably attached to the fiber surface, thereby improving the stability of the antibacterial sustained-release microcapsules, and can maintain the breathability of the fabric and maintain the comfort of the fabric.
[0016] Preferably, the mass ratio of the daylily essence, polyvinyl alcohol and ε-polylysine is 1:1.1:(0.69-0.75).
[0017] By adopting the above technical solution, the mass ratio of daylily essence, polyvinyl alcohol and ε-polylysine is preferably within the above range, which can further improve the comprehensive performance of the prepared antibacterial sustained-release capsules.
[0018] Preferably, the emulsifier comprises Tween-80.
[0019] Preferably, the reaction temperature is 50-60°C.
[0020] Preferably, the wear-resistant coating is prepared by the following method: The coating substrate, antibacterial slow-release microcapsules, wear-resistant components, softeners and defoamers are mixed and stirred to obtain the wear-resistant coating.
[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. A wear-resistant coating is applied on the surface of the graphene air layer of the fabric component, so that a wear-resistant layer is formed on the surface of the graphene air layer. The wear-resistant components in the wear-resistant coating have aramid fiber, dopamine and nano-silicon dioxide components, which can play a good wear-resistant role and can synergistically improve the overall mechanical properties of the wear-resistant coating. The obtained wear-resistant layer can have good wear-resistant performance, thereby improving the overall service life of the physiotherapy pad; 2. Antibacterial sustained-release microcapsules are also added to the wear-resistant filler. The antibacterial sustained-release microcapsules are prepared from daylily essence, ε-polylysine and polyvinyl alcohol. Daylily essence has good antibacterial effect and the volatile components are beneficial to promoting human circulation. The daylily essence is encapsulated in the microcapsule structure so that the daylily essence can be slowly released. On the one hand, the antibacterial sustained-release microcapsules can have a synergistic antibacterial effect with the graphene air layer and the graphene fiber layer. On the other hand, it can further promote the therapeutic pad's promoting effect on human circulation. DETAILED DESCRIPTION
[0022] The present application is further described in detail below with reference to the embodiments: Material description: The coating body is water-based polyurethane; the emulsifier is Tween-80; the chain extender is ethylene glycol ethanol solution with a mass concentration of 8%; the softener is polyethylene glycol, and the defoamer is polysiloxane defoamer; daylily essence was purchased from Chengdu Pusi Biotechnology Co., Ltd.
[0023] Example 1 Preparation of wear-resistant components: 6.13 g of nano-aramid fiber was mixed with 500 g of deionized water to obtain an aramid fiber dispersion, 6.87 g of dopamine (CAS No.: 51-61-6) was added, the pH value was adjusted to 8.5 with Tris buffer, and the mixture was stirred with magnetic force at 600 rpm at 25°C for 24 h. After the reaction, the mixture was washed three times with anhydrous ethanol to obtain dopamine-modified aramid fiber. 12.12 g of dopamine-modified aramid fiber was mixed with 300 g of anhydrous ethanol. After combination, 15 g of ammonia water was added, and after ultrasonication for 30 minutes, the temperature was raised to 30°C at a speed of 600 rpm while magnetically stirring. While maintaining stirring, 7.88 g of ethyl orthosilicate and 2.3 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane (CAS No.: 101947-16-4) were added, and stirring was continued for 4 hours. Then 0.2 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added and stirring was maintained for 3 hours to obtain a wear-resistant component.
[0024] Preparation of antibacterial sustained-release microcapsules: 5.38 g of daylily essence and 2.69 g of isophorone diisocyanate (CAS No.: 4098-71-9) were mixed to obtain an oil phase, 5.91 g of polyvinyl alcohol (CAS No.: 9002-89-5) and 150 g of deionized water were mixed and stirred to obtain a polyvinyl alcohol dispersion, the polyvinyl alcohol dispersion was heated to 50° C., the oil phase was added to the polyvinyl alcohol dispersion, 7 g of emulsifier and 5 g of chain extender were added, and the mixture was stirred at a speed of 600 rpm for 90 min to obtain a daylily essence prefabricated microcapsule emulsion; 3.71 g of ε-polylysine (CAS No.: ε-polylysine) was mixed with 37 g of deionized water to obtain an ε-polylysine aqueous solution, the ε-polylysine aqueous solution was added to the daylily essence prefabricated microcapsule emulsion, the temperature was maintained at 50° C. and the mixture was stirred at a speed of 600 rpm for 90 min to obtain antibacterial sustained-release microcapsules.
[0025] Preparation of wear-resistant coating: 500 g of coating substrate, 60 g of antibacterial slow-release microcapsules, 120 g of wear-resistant components, 12 g of softener and 10 g of defoamer were mixed, and stirred at a speed of 900 rpm for 45 minutes to obtain a wear-resistant coating.
[0026] Prepare the therapy mat: The graphene air layer is completely immersed in the wear-resistant coating so that the wear-resistant coating fully contacts the graphene air layer. After being immersed for 2 hours, the graphene air layer is dried at 45°C for 4 hours to form a wear-resistant layer on the surface of the graphene air layer. The graphene air layer, graphene fiber layer, imitation silk cotton layer, sanded fabric layer, needle cotton layer, sponge layer and fishing net breathable layer with the wear-resistant layer attached are sequentially overlapped, and the three adjacent sides are sewn to obtain a fabric component preform. After finishing, the physical therapy component is filled from the fabric component preform that has not been sewn between the sanded fabric layer and the needle cotton layer. After finishing, the fabric component preform is sewn so that the physical therapy component is covered with the fabric component outside to obtain a physical therapy pad product.
[0027] Example 2 Preparation of wear-resistant components: 5.96 g of nano-aramid fiber was mixed with 500 g of deionized water to obtain an aramid fiber dispersion, 7.04 g of dopamine was added, the pH value was adjusted to 8.5 with Tris buffer, and the mixture was magnetically stirred at 600 rpm at a temperature of 25°C for 24 hours. After the reaction, the mixture was washed three times with anhydrous ethanol to obtain dopamine-modified aramid fiber; 11.83 g of dopamine-modified aramid fiber was mixed with 300 g of anhydrous ethanol, 15 g of ammonia water was added, and after ultrasonic treatment for 30 minutes, the mixture was heated to 30°C with magnetic stirring at 600 rpm, 8.17 g of tetraethyl orthosilicate and 2.3 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added while maintaining stirring, and stirring was continued for 4 hours. Then, 0.2 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added and stirring was maintained for 3 hours to obtain a wear-resistant component.
[0028] Preparation of antibacterial sustained-release microcapsules: 5.26 g of daylily essence and 2.63 g of isophorone diisocyanate were mixed to obtain an oil phase, 5.79 g of polyvinyl alcohol and 150 g of deionized water were mixed and stirred to obtain a polyvinyl alcohol dispersion, the polyvinyl alcohol dispersion was heated to 60° C., the oil phase was added to the polyvinyl alcohol dispersion, 7 g of emulsifier and 5 g of chain extender were added, and the mixture was stirred at a speed of 600 rpm for 90 min to obtain a daylily essence prefabricated microcapsule emulsion; 3.95 g of ε-polylysine was mixed with 40 g of deionized water to obtain an ε-polylysine aqueous solution, the ε-polylysine aqueous solution was added to the daylily essence prefabricated microcapsule emulsion, the temperature was maintained at 60° C. and the mixture was stirred at a speed of 600 rpm for 90 min to obtain antibacterial sustained-release microcapsules.
[0029] Preparation of wear-resistant coating: 560 g of coating substrate, 70 g of antibacterial slow-release microcapsules, 160 g of wear-resistant components, 16 g of softener and 16 g of defoamer were mixed, and stirred at a speed of 900 rpm for 45 minutes to obtain a wear-resistant coating.
[0030] Prepare the therapy mat: The graphene air layer is completely immersed in the wear-resistant coating so that the wear-resistant coating fully contacts the graphene air layer. After being immersed for 2 hours, the graphene air layer is dried at 45°C for 4 hours to form a wear-resistant layer on the surface of the graphene air layer. The graphene air layer, graphene fiber layer, imitation silk cotton layer, sanded fabric layer, needle cotton layer, sponge layer and fishing net breathable layer with the wear-resistant layer attached are sequentially overlapped, and the three adjacent sides are sewn to obtain a fabric component preform. After finishing, the physical therapy component is filled from the fabric component preform that has not been sewn between the sanded fabric layer and the needle cotton layer. After finishing, the fabric component preform is sewn so that the physical therapy component is covered with the fabric component outside to obtain a physical therapy pad product.
[0031] Example 3 Preparation of wear-resistant components: 6.05 g of nano-aramid fiber was mixed with 500 g of deionized water to obtain an aramid fiber dispersion, 6.95 g of dopamine was added, the pH value was adjusted to 8.5 with Tris buffer, and the mixture was magnetically stirred at 600 rpm at a temperature of 25°C for 24 hours. After the reaction, the mixture was washed three times with anhydrous ethanol to obtain dopamine-modified aramid fiber; 11.98 g of dopamine-modified aramid fiber was mixed with 300 g of anhydrous ethanol, 15 g of ammonia water was added, and after ultrasonic treatment for 30 minutes, the mixture was heated to 30°C with magnetic stirring at 600 rpm, 8.02 g of tetraethyl orthosilicate and 2.3 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added while maintaining stirring, and stirring was continued for 4 hours. Then, 0.2 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added and stirring was maintained for 3 hours to obtain a wear-resistant component.
[0032] Preparation of antibacterial sustained-release microcapsules: 5.32 g of daylily essence and 2.66 g of isophorone diisocyanate were mixed to obtain an oil phase, 5.85 g of polyvinyl alcohol and 150 g of deionized water were mixed and stirred to obtain a polyvinyl alcohol dispersion, the polyvinyl alcohol dispersion was heated to 55° C., the oil phase was added to the polyvinyl alcohol dispersion, 7 g of emulsifier and 5 g of chain extender were added, and the mixture was stirred at a speed of 600 rpm for 90 min to obtain a daylily essence prefabricated microcapsule emulsion; 3.83 g of ε-polylysine was mixed with 39 g of deionized water to obtain an ε-polylysine aqueous solution, the ε-polylysine aqueous solution was added to the daylily essence prefabricated microcapsule emulsion, the temperature was maintained at 55° C. and the mixture was stirred at a speed of 600 rpm for 90 min to obtain antibacterial sustained-release microcapsules.
[0033] Preparation of wear-resistant coating: 530 g of coating substrate, 65 g of antibacterial slow-release microcapsules, 140 g of wear-resistant components, 14 g of softener and 13 g of defoamer were mixed, and stirred at a speed of 900 rpm for 45 minutes to obtain a wear-resistant coating.
[0034] Prepare the therapy mat: The graphene air layer is completely immersed in the wear-resistant coating so that the wear-resistant coating fully contacts the graphene air layer. After being immersed for 2 hours, the graphene air layer is dried at 45°C for 4 hours to form a wear-resistant layer on the surface of the graphene air layer. The graphene air layer, graphene fiber layer, imitation silk cotton layer, sanded fabric layer, needle cotton layer, sponge layer and fishing net breathable layer with the wear-resistant layer attached are sequentially overlapped, and the three adjacent sides are sewn to obtain a fabric component preform. After finishing, the physical therapy component is filled from the fabric component preform that has not been sewn between the sanded fabric layer and the needle cotton layer. After finishing, the fabric component preform is sewn so that the physical therapy component is covered with the fabric component outside to obtain a physical therapy pad product.
[0035] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing dopamine-modified aramid fiber, 6.34 g of nano-aramid fiber and 6.66 g of dopamine are used.
[0036] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing dopamine-modified aramid fiber, 5.78 g of nano-aramid fiber and 7.22 g of dopamine are used.
[0037] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, 12.5 g of dopamine-modified aramid fiber and 7.5 g of tetraethyl orthosilicate are used in preparing the wear-resistant component.
[0038] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, 10.87 g of dopamine-modified aramid fiber and 9.13 g of tetraethyl orthosilicate are used in preparing the wear-resistant component.
[0039] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, 5.56 g of daylily essence, 6.11 g of polyvinyl alcohol and 3.33 g of ε-polylysine are used in preparing antibacterial sustained-release microcapsules.
[0040] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, 5.1 g of daylily essence, 5.61 g of polyvinyl alcohol and 4.29 g of ε-polylysine are used in preparing antibacterial sustained-release microcapsules.
[0041] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, when preparing the antibacterial sustained-release microcapsules, the reaction temperature is 45°C.
[0042] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 11, the reaction temperature is 65°C when preparing the antibacterial sustained-release microcapsules.
[0043] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, the grass essence prefabricated microcapsule emulsion is used as the sustained-release antibacterial microcapsule.
[0044] Comparative Example 1 Comparative Example 1 is based on Example 3. In Comparative Example 1, dopamine-modified aramid fiber is ultrasonically dispersed with anhydrous ethanol to prepare a wear-resistant component.
[0045] Performance testing The following performance tests were performed on the physiotherapy pads prepared in Examples 1-12 and Comparative Example 1: (1) Wear resistance test According to ISO5981-2007, the wear resistance of the side of the sample with the wear-resistant layer was tested. Each sample was tested three times, and the average value was taken. The test results were filled in Table 1.
[0046] (2) Hydrophobic performance test The contact angle test was carried out on the side of the sample with the wear-resistant layer attached. The five-point sampling method was adopted. Each sample was tested three times, and the average value was taken. The test results were filled in Table 1.
[0047] (3) Antibacterial performance test Taking GB T 20944.3-2008 Evaluation of Antibacterial Properties of Textiles as the inspection standard, the antibacterial performance test was carried out on the side of the sample with the wear-resistant layer, and the antibacterial rate of the sample was measured after 1 day and 7 days respectively. Each sample was tested three times, and the average value was taken. The test results were filled in Table 1.
[0048] Table 1 Performance test results of Examples 1-13 and Comparative Example 1 Data analysis shows that the wear resistance times of Examples 1-3 are all 6600 times or more, indicating that the therapeutic pad prepared by the present application has good wear resistance, the contact angles of Examples 1-3 are all 160° or more, indicating that the therapeutic pad prepared by the present application has good hydrophobic properties, the antibacterial rates of Escherichia coli in Examples 1-3 are all above 99.5%, and the antibacterial rates of Staphylococcus aureus are all above 99.5%, indicating that the therapeutic pad prepared by the present application has good antibacterial properties. After 7 days of maintenance, the antibacterial rates of Escherichia coli in Examples 1-3 are all 94% or more, and the antibacterial rates of Staphylococcus aureus are all 94% or more, indicating that the therapeutic pad prepared by the present application has long-term antibacterial properties.
[0049] When preparing dopamine-modified aramid fibers in Examples 4 and 5, the mass ratios of nano-aramid fibers to dopamine are not within the range specified in the present application. When the dopamine content is too high, the dopamine layer coated on the aramid limiting surface is too thick, and the mechanical properties of the nano-aramid fibers are difficult to reflect. When the dopamine content is too low, it is difficult to evenly coat the dopamine layer on the surface of the nano-aramid fibers, and the subsequent growth of nano-silicon dioxide is affected, thereby affecting the overall performance of the wear-resistant component. Therefore, the various performances of Examples 4 and 5 are reduced.
[0050] When preparing the wear-resistant components in Examples 6 and 7, the dopamine-modified aramid fiber and tetraethyl orthosilicate used are not within the scope defined in the present application. When the content of tetraethyl orthosilicate is too little, the uniformity of the nano-silica particles grown on the surface of the dopamine layer decreases and the surface roughness is too small, which affects the hydrophobic performance and stability. When the content of tetraethyl orthosilicate is too much, too many nano-silica particles are generated on the surface of the dopamine layer, which affects the dispersion performance of the wear-resistant component and further affects the stability of the wear-resistant coating. Therefore, the various performances between Examples 6 and 7 are reduced.
[0051] In the preparation of antibacterial sustained-release microcapsules in Examples 8 and 9, the mass ratios of daylily essence, polyvinyl alcohol and ε-polylysine are not within the range specified in the present application. When the content of ε-polylysine is too little, the modification effect on the microcapsules is weak, the surface smoothness of the microcapsules is large, and the adhesion effect with the fabric is poor, which affects the stability of the antibacterial sustained-release capsules. When the content of ε-polylysine is too much, the particle size of the prepared antibacterial sustained-release microcapsules is too large, so that the particle size of the prepared antibacterial sustained-release microcapsules is different, which affects the stability of the antibacterial sustained-release microcapsules. Therefore, the performance of Examples 8 and 9 is reduced.
[0052] When preparing the antibacterial sustained-release microcapsules in Examples 10 and 11, the reaction temperature is not within the range specified in the present application. When the reaction temperature is too low, it is difficult for the components to disperse, so the interfacial polymerization reaction effect is poor, which affects the stability of the antibacterial sustained-release microcapsules. When the reaction temperature is too high, the various reactions in the system are too fast, which inhibits the formation of macromolecular polymers, thereby affecting the preparation of the antibacterial sustained-release microcapsules. Therefore, the performance of Examples 10 and 11 is reduced.
[0053] In Example 12, ε-polylysine was not used to modify the preformed microcapsules of daylily essence. On the one hand, the surface smoothness of the preformed microcapsules of daylily essence was difficult to improve, and the bonding effect with the fabric fibers was reduced. On the other hand, without adding ε-polylysine, it was difficult to further protect the daylily essence, the thermal stability was reduced, and the daylily essence was lost too quickly, making it difficult to achieve a long-term antibacterial effect.
[0054] In Comparative Example 1, the wear-resistant component is only a mixture of dopamine-modified aramid fiber and anhydrous ethanol, and the aramid fiber without adding tetraethyl orthosilicate does not generate nano-silicon dioxide on the surface. Therefore, the wear resistance and hydrophobicity are reduced.
[0055] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A microcirculation therapy pad, characterized in that: It includes a physical therapy component and a fabric component, the fabric component is coated on the outside of the physical therapy component, the fabric component includes a wear-resistant layer, a graphene air layer, a graphene fiber layer, a silk-like cotton layer, a sanded fabric layer, a needle cotton layer, a sponge layer and a desired breathable layer, the physical therapy component is located between the sanded fabric and the needle cotton fabric, the wear-resistant layer is obtained by coating a wear-resistant coating on the surface of the graphene air layer, and the wear-resistant coating includes the following components by mass: 500-560 parts of coating substrate, 60-70 parts of antibacterial slow-release microcapsules, 120-160 parts of wear-resistant components, 12-16 parts of softeners, and 10-16 parts of defoaming agents; The wear-resistant component includes aramid fiber, dopamine and silicon dioxide.
2. A microcirculation therapy pad according to claim 1, characterized in that: The wear-resistant component is prepared by the following method: The nano-aramid fiber is mixed with deionized water to obtain an aramid fiber dispersion, dopamine is added, the pH value is adjusted to alkaline, the reaction is stirred, and the reaction is washed to obtain dopamine-modified aramid fiber; the dopamine-modified aramid fiber is mixed with anhydrous ethanol, ammonia water is added, and after ultrasonication, the temperature is increased while stirring, and ethyl orthosilicate and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane are added under the stirring condition, and the stirring is continued for 4 hours, and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane is further added to keep stirring for 3 hours to obtain a wear-resistant component.
3. A microcirculation therapy pad according to claim 2, characterized in that: The mass ratio between the aramid limiter and dopamine is 1:(1.12-1.18).
4. A microcirculation therapy pad according to claim 2, characterized in that: The mass ratio between the dopamine-modified aramid fiber and tetraethyl orthosilicate is 1:(0.45-0.49).
5. The microcirculation therapy pad according to claim 1, characterized in that: The antibacterial sustained-release microcapsules include daylily essence polyvinyl alcohol and ε-polylysine.
6. A microcirculation therapy pad according to claim 5, characterized in that: The antibacterial sustained-release microcapsules are prepared by the following method: The oil phase is obtained by mixing daylily essence with isophorone diisocyanate, polyvinyl alcohol is mixed with deionized water to obtain a polyvinyl alcohol dispersion, the polyvinyl alcohol dispersion is heated to a reaction temperature, the oil phase is added to the polyvinyl alcohol dispersion, an emulsifier and a chain extender are added and stirred to obtain a daylily essence prefabricated microcapsule emulsion; ε-polylysine is mixed with deionized water to obtain an ε-polylysine aqueous solution, the ε-polylysine aqueous solution is added to the daylily essence prefabricated microcapsule emulsion, the reaction temperature is maintained and stirred to obtain antibacterial sustained-release microcapsules.
7. The microcirculation therapy pad according to claim 5, characterized in that: The mass ratio of the daylily essence, polyvinyl alcohol and ε-polylysine is 1:1.1:(0.69-0.75).
8. The microcirculation therapy pad according to claim 6, characterized in that: The emulsifier includes Tween-80.
9. The microcirculation therapy pad according to claim 6, characterized in that: The reaction temperature is 50-60°C.
10. The microcirculation therapy pad according to claim 1, characterized in that: The wear-resistant coating is prepared by the following method: The coating substrate, antibacterial slow-release microcapsules, wear-resistant components, softeners and defoamers are mixed and stirred to obtain the wear-resistant coating.
Citation Information
Patent Citations
Efficient graphene physiotherapy cushion and production method
CN112841996A
Antibacterial coating essence microcapsule and method
CN116411460A
Aramid fiber electrochemical capacitor and preparation method therefor
US20200294731A1
Rolling-massaging mattress or cushion
US5416936A
High-elasticity heat-resistant nylon 6 and preparation method
WO2019210587A1